Development of Semiquantitative Food Frequency Questionnaire for Identification of Indigenous Dietary Patterns in Prediabetic Adult Women - Nuryani, Nuryani; Khomsan, Ali; Dwiriani, Cesilia Meti; Dewi, Mira; Lukito, Widjaja (Universitas Airlangga, 2024)
Dietary patterns influence the progression of prediabetes, so it is necessary to develop representative instruments for measuring eating habits, primarily indigenous dietary consumption. The research aimed to develop a semiquantitative food frequency questionnaire to identify indigenous dietary patterns in prediabetes sufferers in Gorontalo Regency. The research was a descriptive study that tested the validity and reliability of the food frequency questionnaire semiquantitative (FFQ-SQ). The research was conducted in Limboto Barat Health Center, based on the prevalence of diabetes mellitus. Selection samples using purposive sampling with 30 adult women. The validity test used internal validity Pearson correlation, while the reliability test used internal consistency Cronbach α. Comparison of average FFQ-SQ and recall 2 x 24-hours using Wilcoxon test. The results showed that 12 food groups consisted of 207 food items and indigenous food products with validity tests 123 items valid, 67 items invalid, and 17 items never consumed by the subject study in the previous month; the reliability test showed food group category low 10, moderate 5 and high 3. Comparative analysis of the energy and nutrient intake between FFQ-SQ with recall 2 x 24 hours showed significant differences in intake of carbohydrates, fiber, vitamin E, vitamin B1, folic acid, vitamin C, potassium and zinc (p-value < 0.005), and comparison of energy and nutrient intake between FFQ-SQ1 and FFQ-SQ2 showed no significant difference (p-value> 0.005). The conclusion was FFQ-SQ with 123 items of foods and derived products is valid and reliable for measuring the eating habits of prediabetic adult women.